An Extremely Luminous Panchromatic Outburst from the Nucleus of a Distant Galaxy - Levan, A.; Tanvir, N.; Cenko, S.; Perley, D.; Wiersema, K.; Bloom, J.; Fruchter, A.; de Ugarte Postigo, A.; O’Brien, P.; Butler, N.; van der Horst, A.; Leloudas, G.; et al. (The American Association for the Advancement of Science, 2011)
Variable x-ray and g-ray emission is characteristic of the most extreme physical processes inthe universe. We present multiwavelength observations of a unique g-ray–selected transientdetected by the Swift satellite, accompanied by bright emission across the electromagneticspectrum, and whose properties are unlike any previously observed source. We pinpoint theevent to the center of a small, star-forming galaxy at redshift z = 0.3534. Its high-energyemission has lasted much longer than any g-ray burst, whereas its peak luminosity was~100 times higher than bright active galactic nuclei. The association of the outburst with thecenter of its host galaxy suggests that this phenomenon has its origin in a rare mechanisminvolving the massive black hole in the nucleus of that galaxy.